2016
DOI: 10.1097/01.prs.0000475772.91525.26
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon Reimbursements in Maxillofacial Trauma Surgery

Abstract: After implementation of the Affordable Care Act, we observed a significant reduction in the proportion of maxillofacial trauma patients who were uninsured. Surgeons' overall reimbursement rate increased. These trends should be followed over a longer term to determine the full effect of the Affordable Care Act.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…Previous research has found that the image of destination has a significant and positive effect on the intention of returning visits Pratminingsih et al (2014); Setyaningsih & Murwatiningsih (2017). However, the research results by Khansa & Farida, (2016) prove that image of the destination do not affect the intention to return. Creating the intention to visit again can be done thru the behavior of visitors' motivation or the quality of services offered by a destination.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Previous research has found that the image of destination has a significant and positive effect on the intention of returning visits Pratminingsih et al (2014); Setyaningsih & Murwatiningsih (2017). However, the research results by Khansa & Farida, (2016) prove that image of the destination do not affect the intention to return. Creating the intention to visit again can be done thru the behavior of visitors' motivation or the quality of services offered by a destination.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Estas melhorias podem ser atribuídas à correção de insatisfações estéticas que possam afetar negativamente o bem-estar emocional dos pacientes, contribuindo para uma maior aceitação de sua aparência e uma melhor qualidade de vida. No entanto, é importante considerar que os resultados podem variar de acordo com características individuais e contextuais, como idade, sexo, histórico médico, expectativas préoperatórias, cultura e expectativas sociais (Fonseca et al, 2014;Javo et al, 2010;Khansa et al, 2016;von Soest et al, 2012).…”
Section: Discussionunclassified
“…Ennek egyik oka a kü-lönböző betegbiztosítási és finanszírozási rendszerekben keresendő. Példaként említhetjük az Egyesült Államo-kat, ahol a fej-nyak terület traumatológiai ellátásának költségeit mindössze alig 40%-ban finanszírozzák, ami arra vezethető vissza, hogy a pácienseknek csak kis száza-léka rendelkezik megfelelő biztosítással [8]. Szakmai szempontból viszont ez a szakterület rendkívül összetett és számos társszakma alapos ismeretét igényli.…”
Section: Megbeszélésunclassified